Identifying Key Service and Quality Dimensions as Public Relations Strategy in RSUP Persahabatan - Soleha soleha; Anggayuh Gesang Utomo; Noprita Herari (Lingkar Studi Komunikasi (LISKI), 2023)
This study aims to determine the Application of the SERVQUAL Model to the PENCILS Public Relations Strategy at KS Hukormas (Organizational Legal Substance and Public Relations Substance Group) Persahabatan Hospital. The importance of the existence of public relations in health institutions, not only as forming a positive image of the hospital in synergy with internal and external customers, but also playing an active role in managing various health issues through community-focused activities. The dimensions of service quality (SERVQUAL) consisting of Tangible, Assurance, Reliability, Responsiveness and Empathy (TARRE), are parameters in the KS Hukormas RSUP Persahabatan in carrying out PR activities through the PENCILS strategy (Publications, Events, News, Community Involvement, Lobbying and Negotiation and social responsibility). This descriptive qualitative research uses multiple methods in data collection: observation, interviews and literature study. The results of the study show that although all aspects of TARRE have been fulfilled in PENCILS activities, the internal opinion of the RSUP Persahabatan considers that several aspects still need to be optimized and varied so that they are more interesting and not monotonous. Keywords: SERVQUAL Model, PENCILS PR Strategy, Hospital Public Relations, Health Communication